The Transformation of Islamic Educational Institutions in Indonesia: A Systematic Literature Review on Pesantren, Madrasah, and Islamic Full Day Schools - Ibnu Rizqulloh; Muh. Nur Rochim Maksum; Istanto Istanto (Universitas Muhammadiyah Surakarta, 2025)
This study examines the transformation of Islamic educational institutions in Indonesia including pesantren, madrasah, and integrated Islamic schools in responding to the dynamics of modernity and the globalization of education. The background of this research stems from the need to understand how Islamic educational institutions can adapt to the demands of the digital era without abandoning the Islamic values that form their fundamental identity. The main objective of this study is to analyze the forms, directions, and implications of institutional transformation within Indonesia’s Islamic education through a qualitative, literature based approach employing an integrative literature review strategy. Data were collected from various scholarly sources, including reputable journals, academic books, and relevant research reports, and were analyzed thematically and narratively. The findings reveal that the transformation of Islamic education occurs across three major dimensions: institutional, curricular, and ideological values. Pesantren are experiencing modernization in management and curriculum, madrasah emphasize the integration of religious and general sciences, while integrated Islamic schools represent a new, holistic, and adaptive model of Islamic education. Collectively, these institutions demonstrate a synergistic pattern in shaping a more inclusive and competitive national Islamic education system. Theoretically, this study contributes to strengthening the integrative paradigm between faith, knowledge, and practice, while practically providing a conceptual foundation for developing Islamic education policies and strategies that are relevant to the challenges of the modern era.